2021
DOI: 10.3390/cancers13205117
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Neuroendocrine Tumors: Molecular Mechanisms and Therapeutic Targets

Abstract: Pancreatic neuroendocrine tumors (pNETs) are unique, slow-growing malignancies whose molecular pathogenesis is incompletely understood. With rising incidence of pNETs over the last four decades, larger and more comprehensive ‘omic’ analyses of patient tumors have led to a clearer picture of the pNET genomic landscape and transcriptional profiles for both primary and metastatic lesions. In pNET patients with advanced disease, those insights have guided the use of targeted therapies that inhibit activated mTOR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 347 publications
(623 reference statements)
0
33
0
Order By: Relevance
“…Recently, studies were investigated on belzutifan, development code: MK-6482, which is a hypoxia-inducible factor-2α (HIF-2α) inhibitor for the treatment of adult patients with Hippel-Lindau syndrome. This agent is not FDA approved in US and had a 83% response rate in PNETs (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies were investigated on belzutifan, development code: MK-6482, which is a hypoxia-inducible factor-2α (HIF-2α) inhibitor for the treatment of adult patients with Hippel-Lindau syndrome. This agent is not FDA approved in US and had a 83% response rate in PNETs (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Combining the results, KRAS mutation might be an important diver mutation of composite IPMN-NET. Since the status of KRAS have been studied in pure IPMN and NEN in multiple studies, we further searched COSMIC database for the information of the other two mutated genes ( PCK1 and MLL3 ) in pancreatic neoplasms (Table 2 ) [ 46 48 ]. We found that most PCK1 mutations occur in pancreatic ductal adenocarcinoma (several samples with unknown histology subtype).…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis in patients with advanced pancreatic neuroendocrine neoplasms (panNENs) has been generally poor and, until recently, there has been little improvement, mainly due to the lack of new therapeutic approaches which have led to effective anti-tumor treatment activity in these patients [ 7 , 9 , 11 , 12 , 13 , 14 , 15 ]. In the past decade, however, there has been significant advances, not only in the treatment approaches for panNEN patients with advanced disease, the recognition into the pathogenesis of the acquired and primary resistance to anti-tumor treatment which is an increasing problem, but also in the diagnosis, management and overall treatment of panNENs, as well as other NENs, which is beginning to influence survival rates in these patients [ 7 , 11 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. We have recently analyzed both these advances and controversies in identifying prognostic factors for the overall management of panNEN patients, as well as for surgical outcomes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these recent advances, resistance to anti-tumor therapies, either primary resistance or acquired resistance, in patients with advanced PanNENs, is an increasing problem [ 6 , 20 , 21 , 29 , 75 , 76 , 77 , 78 , 79 ]. This is a similar finding to its occurrence with similar anti-tumor treatments in patients with other non-NEN advanced malignancies [ 80 ], as well as patients with advanced NENs in other non-pancreatic locations (i.e., carcinoids) [ 6 , 29 , 76 , 77 , 78 , 79 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation